Beadchip molecular immunohematology toward routine donor and patient antigen profiling by DNA analysis - Edwards-Moulds, JoAnn; Ness, Paul M.; Sloan, Steve R.; SpringerLink (Online service). (New York Springer, 2011)
First book on the market to be used for courses such as: Specialist in Blood Banking ("SBB") and other accreditation programs in molecular immunohematology for Hospital and Blood Bank Transfusion Services, Transfusion Medicine, and reference laboratories. Offers thorough review of molecular immunohematology, particularly the BeadChip technology developed by BioArray Solutions Draws from analyses and case studies around the world, detailing techniques used in many labs. We have entered the era of molecular immunohematology in which DNA is analyzed to predict red blood cell and platelet phenotypes. Indeed, many laboratories and blood banks across the world have already adopted and implemented molecular techniques. Some fear that serology is now becoming outdated, but immunohematology techniques often supplement the work of serologists, and several leading serology laboratories are the very same ones that were early adopters of molecular immunohematology. This book is a thorough review of molecular immunohematology and is aimed at anyone interested in how it is changing blood bank and transfusion medicine. BeadChip Molecular Immunohematology opens with a history of serology before it provides an overview of gene expression, how genetic variations translate into antigenic differences on the surfaces of cells, and techniques that have been developed to detect genetic variations. It then describes in detail the BeadChip technology developed by BioArray Solutions, the molecular immunohematology system that has been most widely adopted in blood blank laboratories. The remainder of the book focuses on analyses and case studies from around the world to describe how molecular immunohematology is being used in various settings for various purposes. It includes a discussion of the significant advances that have been made to incorporate Rh testing on the BeadChip platform as well as the potential use of that system
Chapter 1: An overview of the Classical Serological methods: limitations and benefits of serology and DNA testing John J. Moulds Chapter 2: Introduction to Molecular Typing Joann M. Moulds, Steven R. Sloan Chapter 3: The BeadChip System: A Flexible Array Format for Complex Nucleic Acid and Protein Analysis Ghazala Hashmi, Yi Zhang, Michael Seul Chapter 4: Implementation of HEA at Blood Centers: Prescreening, Rare Donors, Inventory Management Joann M. Moulds Chapter 5: Implementation of HEA BeadChip System at Medical Centers: Providing Extended Matched Units and Eliminating Complex Workups for Patients Ellen Klapper Chapter 6: Human Platelet Antigen Genotyping and Diagnosis of Antiplatelet Alloimmunization Gerald Bertrand, Cecile Kaplan-Gouet Chapter 7: Blood group genotyping by high-throughput DNA-analysis: Application to the Panel National de Référence du CNRGS Sandrine Kappler-Gratias, Thierry Peyrard, Pierre Yves Le Pennec, Jean-Pierre Cartron, Philippe Rouger, Bach-Nga Pham Chapter 8: Implementation and Assessment of High-Throughput Donor Typing at the Milan, Italy Immunohematology Reference Laboratory Nicoletta Revelli, Cinzia Paccapelo, Paola Ponzo, Francesca Truglio, Veronica Sala, Francesca Poli, Maurizio Marconi, Maria Antonietta Villa Chapter 9: Implementation of the BioArray Erythrocyte Antigen (HEA) genotyping System BeadChip? HEA: The Red Cross of Spain Experience Luisa Barea García, Marta Martinez Sánchez, Gemma Cabrera Rodriguez-Escalona, Emma Castro Izaguirre Chapter 10: Looking Beyond HEA: Matching SCD Patients for RH Variants Marion E Reid, Christine Halter Hipsky Chapter 11: Identification of Altered RHD and RHCE Alleles: A Comparison of Manual and Automated Molecular Methods Sunitha Vege, Connie M. Westhoff Chapter 12: Bayesian Classification Algorithms for Automated Allele Assignment Kairali Podual, Yi Zhang, Natalia Mezokh, JiaCheng Yang, Randall Wilson
Title from title screen (viewed September 25, 2023)
Electronic reproduction
Keywords: Blood -- Transfusion; Immunology; Medical laboratories; Medicine; Monoclonal antibodies; Blood group antigens -- Immunology; Blood Banks; Blood grouping and crossmatching -- Methods; Gene expression profiling; Oligonucleotide array sequence analysis -- Methods